The first five years of the Croatian Intelligence Service: 1993-1998 - Tuđman, Miroslav (Array, 2000)
After the first democratic, multiparty elections held in 1990, the process of building state institutions commenced within the framework of newly-sovereign Croatia. This article describes the development of the national security system: the history of the Croatian Intelligence Service and the Intelligence Community, and their origin, structure, tasks and activities. The first five years (1993-1998) of the national security system of the Republic of Croatia are presented in detail and evaluated. HIS was formed in 1993 as a central agency of the National Security Office (UNS). The main objectives were the liberation of Croatias occupied territories and dealing with the regional crisis. HIS was also oriented toward co-operation and partnership with foreign intelligence agencies regarding intelligence assessments of the regional crisis and support of the international troops (UNPROFOR, UNCRO, IFOR, SFOR, etc). The author stresses the legal and ethical criteria upon which HIS and Croatian intelligence community were established.